2020
DOI: 10.1212/wnl.0000000000008861
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of omaveloxolone in patients with mitochondrial myopathy

Abstract: ObjectiveTo investigate the safety and efficacy of escalating doses of the semi-synthetic triterpenoid omaveloxolone in patients with mitochondrial myopathy.MethodsIn cohorts of 8–13, 53 participants were randomized double-blind to 12 weeks of treatment with omaveloxolone 5, 10, 20, 40, 80, or 160 mg, or placebo. Outcome measures were change in peak cycling exercise workload (primary), in 6-minute walk test (6MWT) distance (secondary), and in submaximal exercise heart rate and plasma lactate (exploratory).Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 23 publications
4
31
0
Order By: Relevance
“…While there is very little evidence regarding therapeutic options arising from oxidative stress in mtDNA-associated diseases, a pilot study using a combination of different antioxidants has gained promising results [ 72 , 73 ]. In contrast, the results of a recently published phase I/II clinical trial focusing on omaveloxolone as potent inductor of Nrf2-signalling did not show a significant change in muscle weakness (measured by exercise workload and 6-min walk test), while submaximal exercise heart rate and plasma lactate were significantly lowered [ 74 ]. The small cohort size (8–13 participants per dosing group), as well as the short treatment period (12 weeks), may be considered as reasons for not meeting the efficacy endpoint.…”
Section: Oxidative Stress Responsementioning
confidence: 99%
“…While there is very little evidence regarding therapeutic options arising from oxidative stress in mtDNA-associated diseases, a pilot study using a combination of different antioxidants has gained promising results [ 72 , 73 ]. In contrast, the results of a recently published phase I/II clinical trial focusing on omaveloxolone as potent inductor of Nrf2-signalling did not show a significant change in muscle weakness (measured by exercise workload and 6-min walk test), while submaximal exercise heart rate and plasma lactate were significantly lowered [ 74 ]. The small cohort size (8–13 participants per dosing group), as well as the short treatment period (12 weeks), may be considered as reasons for not meeting the efficacy endpoint.…”
Section: Oxidative Stress Responsementioning
confidence: 99%
“…However, treatment resulted in reduced heart rate and lactate levels during submaximal exercise, indicating improved mitochondrial function and submaximal exercise tolerance. The authors suggested further studies need to be conducted with a more homogenous population, and a larger number of patients [ 74 ] ( https://clinicaltrials.gov/ct2/show/NCT02255422 ).…”
Section: Augmentation Of Mitochondrial Biogenesismentioning
confidence: 99%
“…NRF2 is a promising therapeutic target with antiinflammatory and antioxidation effects because it regulates the expression of genes related to inflammation, redox metabolism and proteostasis (Liu et al 2016). Madsen et al (2020) tried to prove its effect among 53 patients with MM (18 with CPEO, one with KSS, two with Leigh syndrome, five with MELAS, four with myoclonic epilepsy associated with ragged-red fibers, two with neuropathy, ataxia and retinitis pigmentosa and 21 with unclear disease) with a multicenter double-blind, randomized, placebo-controlled trial. Patients received omaveloxolone at 5, 10, 20, 40, 80 or 160 mg or placebo once daily for 12 weeks.…”
Section: Omaveloxolonementioning
confidence: 99%